TELEPARALLEL DARK ENERGY MODEL WITH FERMIONIC FIELD FOR BIANCHI TYPE I SPACETIME - Myrzakul S.R; Yerzhanov K.K; Kenzhalin D. Zh; Myrzakulov K.R (Academic Scientific Journal of Computer Science, 2019)
The search for constituents that can explain the periods of accelerating expansion of the Universe is a fundamental topic in cosmology. In the present work, we consider a model with a fermionic field that is nonminimally coupled to gravity in the framework of teleparallel gravity for Bianchi type I spacetime. Here we determined form the point-like Lagrangian and obtained the corresponding field equations. In order to determine forms of the coupling and potential function of fermionic field for the considered model, we use Noether symmetry approach. In modern cosmology, we often used this approach to determine the unknown function and obtain exact cosmological solutions for considered model. For our model, we obtained of the coupling and fermionic field functions as F  F0 andV  V0  . Then, we put these solutions to the field equations, we got the equation depend only on the functions A, B and C. After some mathematical calculations, we found exact solutions for these functions as de Sitter solutions. Finally, we determined the equation of state parameter is equal to 1. In cosmology this solution gives us dark energy model and which can describes the late-time epoch of the evolution our universe. Thus, here the fermion fields play the role of dark energy.